Invasion alert: New record of the exotic Gambusia holbrooki Girard, 1859 in the Puna Austral region, Northwestern of Argentina - Andreoli Bize, Julieta (2019)
We report the first record of Gambusia holbrooki Girard, 1859 at elevations above 1,615 m in the Puna Austral, Provincia Catamarca, Argentina. This fish was introduced by intentional release. The Puna is characterized by an endorheic system, where the exotic species would cause a negative impact on the aquatic fauna by predation of eggs and larvae of native fish. Unfortunately, Argentinian conservation policies are directed to protect exotic fish before endemic ichthyofauna.